that follow. 4x – 9y = 7 –2x + 3y = 4 What number would you multiply the second equation by in order to eliminate the x-terms when adding t

Question

that follow. 4x – 9y = 7 –2x + 3y = 4 What number would you multiply the second equation by in order to eliminate the x-terms when adding to the first equation? What number would you multiply the second equation by in order to eliminate the y-terms when adding to the first equation?

in progress 0
Caroline 2 weeks 2021-09-09T13:44:59+00:00 1 Answer 0

Answers ( )

    0
    2021-09-09T13:46:06+00:00

    Answer:

    Step-by-step explanation:

    4x – 9y = 7

    –2x + 3y = 4 (2)

    You want to eliminate the x-terms when adding to the first equation, so you have to multiple both sides of the equation (2) by 2 like:

    4x – 9y = 7

    –4x + 6y = 8

    —————————–(add)

    0 – 3y = 15

    or y = -5, and x = – 19/2

    But if you want to eliminate the y-terms when adding to the first equation, so you have to multiple both sides of the equation (2) by 3, like

    4x – 9y = 7

    -6x + 9y = 12

    —————–(add)

    -2x + 0 = 19

    or x = – 19/2 and y = – 5

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )